Second harmonic generation and two-photon luminescence from colloidal gold nanoparticles. (8th February 2016) - Yashunin, D A; Korytin, A I; Smirnov, A I; Stepanov, A N
Abstract: Second harmonic generation and two-photon luminescence from colloidal gold nanoparticles in the 980–1300 nm wavelength range of exciting femtosecond radiation were investigated experimentally. The measured polarization and spectral characteristics of the second harmonic and two-photon luminescence demonstrate that the observed nonlinear optical signal is determined by the dimers constituting several percent of the total nanoparticle number.